Design and Simulation of an Instrumentation and Control System for the Dosing of Hydroponic Vegetable Crops (LACCEI, 2024)
This paper presents the design of an instrumentation and control system for the dosing of nutrients in a hydroponic vegetable crop. For this crop, a mixture of nitrogen, calcium, potassium, phosphorus, sulfur, magnesium and water is necessary to ensure that the vegetables receive the concentration of nutrients required for their development. For this purpose, an instrumentation system was designed that senses the pH of the nutrient mixture and the ambient temperature, as well as doses the amount of each nutrient according to the type of vegetable. By default, a dosage was programmed to feed chard, spinach, curly lettuce and purple lettuce. The design suggests the use of a programmable Arduino Uno board, which communicates with LabVIEW® for interaction with the user, monitoring and data storage in a computer. The developed project seeks to have a system that allows the reduction of harvesting times and the improvement of product quality, through the monitoring of external variables and the amount of nutrients supplied to the vegetables.